Low-symmetry monoclinic phases and polarization rotation path mediated by epitaxial strain in multiferroic BiFeO3 thin films - Chen, Zuhuang (2012)
A morphotropic phase boundary driven by epitaxial strain has been observed in lead-free multiferroic BiFeO3 thin films and the strain-driven phase transitions have been widely reported as iso-symmetric Cc-Cc by recent works. In this paper, it is suggested that the tetragonal-like BiFeO3 phase identified in epitaxial films on (001) LaAlO3 single crystal substrates is monoclinic MC. This MC phase is different from the MA type monoclinic phase reported in BiFeO3 films grown on low mismatch substrates, such as SrTiO3. This is confirmed not only by synchrotron X-ray studies but also by piezoresponse force microscopy measurements. The polarization vectors of the tetragonal-like phase lie in the (100) plane, not the (110) plane as previously reported. A phenomenological analysis is proposed to explain the formation of MC Phase. Such a low-symmetry MC phase, with its linkage to MA phase and the multiphase coexistence open an avenue for large piezoelectric response in BiFeO3 films and shed light on a complete understanding of possible polarization rotation paths and enhanced multiferroicity in BiFeO3 films mediated by epitaxial strain. This work may also aid the understanding of developing new lead-free strain-driven morphotropic phase boundary in other ferroic systems.